The REGALE Library: A DDS Interoperability Layer for the HPC PowerStack - Giacomo Madella; Federico Tesser; Lluis Alonso; Julita Corbalan; Daniele Cesarini; Andrea Bartolini (Journal of Low Power Electronics and Applications)
Large-scale computing clusters have been the basis of scientific progress for several decades and have now become a commodity fuelling the AI revolution. Dark Silicon, energy efficiency, power consumption, and hot spots are no longer looming threats of an Information and Communication Technologies (ICT) niche but are today the limiting factor of the capability of the entire human society and a contributor to global carbon emissions. However, from the end user, system administrators, and system integrator perspective, handling and optimising the system for these constraints is not straightforward due to the elevated degree of fragmentation in the software tools and interfaces which handles the power management in high-performance computing (HPC) clusters. In this paper, we present the REGALE Library. It is the result of a collaborative effort in the EU EuroHPC JU REGALE project, which aims to effectively materialize the HPC PowerStack initiative, providing a single layer of communication among different power management tools, libraries, and software. The proposed framework is based on the data distribution service (DDS) and real-time publish–subscribe (RTPS) protocols and FastDDS as their implementation. This enables the various actors in the ecosystem to communicate and exchange messages without any further modification inside their implementation. In this paper, we present the blueprint, functionality tests, and performance and scalability evaluation of the DDS implementation currently used in the REGALE Library in the HPC context.